(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
This study established the sanitation stakeholder’s preference for the most suitable type of sanitation technology for the informal settlement. Manual pit emptiers had formed a community-based organization that was supported by a container-based sanitation company. The container-based sanitation company supported the CBO pit emptiers through provision of a transfer station that had a septic tank for containment of liquid waste. The household users were grouped into three: households’ tenants’ toilets, landlords of households’ toilets and caretakers or landlord representative of households’ toilets. The study adopted descriptive case study research design that enabled collection and analysis of both quantitative and qualitative data in Mukuru Kwa Rueben and Mukuru kwa Njenga. Semi-structured questionnaires were used as primary collection tools, collection technique included observation, pictures, and in-depth interviews with stakeholders. Quantitative data was analyzed using SPSS Version 20.0, qualitative data was presented in a reported way. There is insufficient research on stakeholder preference in informal settlements. Although some studies have been conducted on slum sanitation, no published study has explored stakeholder preferences in sanitation technologies specifically in these study areas. The study will give baseline information on the sanitation preference of the stakeholders in Mukuru kwa Njenga and Mukuru kwa Rueben in Nairobi, Kenya.The study established that CBS service provision was the most preferred sanitation technology among 39.2% of the household tenants, 55% among the landlords, 40% caretakers. The results from this study can be applied by the container-based company providers operating and sanitation service providers in low-income high-density settlement for scaling up emptying practices and sanitation technologies.